The Effect of Lockdown and Physical Activity on Glycemic Control in Italian Children and Young Patients With Type 1 Diabetes - Minuto, Nicola; Bassi, Marta; Montobbio, Carolina; Vinci, Francesco; Mercuri, Claudia; Perri, Francesca Nastasia; Cabri, Mara; Calevo, Maria Grazia; d’Annunzio, Giuseppe; Maghnie, Mohamad (Frontiers in Endocrinology, 2021)
Aims The purpose of the study was to evaluate the impact of the lockdown established by the Italian government to limit the spread of Coronavirus disease (COVID-19) on glycemic control in a large sample of patients with type 1 diabetes (T1D) based on age, type of insulin therapy, number of telemedicine visits and physical activity. Material and Methods We retrospectively evaluated glycemic control in young T1D patients using the DexcomG6® system before the Italian lockdown (February 10–23, 2020—Time 0) and during lockdown (April 17–30, 2020—Time 1). Data on age, type of insulin therapy, number of telemedicine visits and physical activity of 202 patients with T1D and a median age of 18.2 years (range: 6–39) were collected. Results Data showed a significant improvement of TIR from 54.58% at T0 to 59.09% at T1 (p ≤0.0001). Glycemic control improved significantly in patients ≥14 years old, showing the best outcome in the “university students and young adults” group (55.40% at T0 and 61.37% at T1, p ≤0.001). All patients reduced physical activity during lockdown; in the 56 patients of “intense physical activity” group both at T0 and T1 TIR increased from ±56.91 to 64.11% (p ≤0.0001). Conclusions Overall, the lockdown led to an unexpected improvement in glycemic control of young patients with T1D. A healthier and stressless lifestyle changes in association with the maintenance of physical activity resulted in a significant age-proportional improvement in glycemic control.